2019
DOI: 10.1021/acs.est.8b05235
|View full text |Cite
|
Sign up to set email alerts
|

Perfluoroalkyl Acids (PFAAs) Concentrations and Oxidative Status in Two Generations of Great Tits Inhabiting a Contamination Hotspot

Abstract: The ubiquity of perfluoroalkyl acids (PFAAs) contrasts with the limited information about their effects. We report here PFAA plasma concentrations in wild populations of great tits (Parus major) settled at and in the vicinity of a fluorochemical plant in Antwerp (Belgium). Using two generations we obtained novel results on some poorly known issues such as differences between sexes, maternal transfer of the compounds and potential associations with the oxidative status. For five out of the 13 detected PFAAs, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 61 publications
(157 reference statements)
4
42
1
Order By: Relevance
“…For example, one of the highest reported fish PFOS concentrations (maximum 9349 ng/g dry wt in whole fish tissue) was from an AFFF-impacted site downstream from Barksdale Air Force Base in Louisiana (Lanza et al 2017). Many biomonitoring studies have identified elevated exposures to legacy and emerging PFAS as the result of industrial activities (Custer et al 2012(Custer et al , 2014Liu et al 2017;Groffen et al 2019;Lopez-Antia et al 2019;Guillette et al 2020). Legacy PFAS such as PFOS are still abundant at many contaminated sites, and novel PFAS are increasingly being detected.…”
Section: Current Understanding Of Pfas Exposure In Wildlifementioning
confidence: 99%
“…For example, one of the highest reported fish PFOS concentrations (maximum 9349 ng/g dry wt in whole fish tissue) was from an AFFF-impacted site downstream from Barksdale Air Force Base in Louisiana (Lanza et al 2017). Many biomonitoring studies have identified elevated exposures to legacy and emerging PFAS as the result of industrial activities (Custer et al 2012(Custer et al , 2014Liu et al 2017;Groffen et al 2019;Lopez-Antia et al 2019;Guillette et al 2020). Legacy PFAS such as PFOS are still abundant at many contaminated sites, and novel PFAS are increasingly being detected.…”
Section: Current Understanding Of Pfas Exposure In Wildlifementioning
confidence: 99%
“…Toxicology and field studies suggest associations between PFAS concentrations and reproductive parameters, morphometric characteristics, and metabolic processes in avifauna. Controlled studies across multiple taxa, including birds, also suggest variable associations between PFAS and lipid production, metabolism, and storage pathways. However, comprehensive assessments of PFAS exposure or potential toxicity in wild avifauna are stymied by a lack of foundational data detailing the environmental occurrence of diverse PFAS across multiple habitats and bird taxa. Transfer of PFAS via trophic interactions is likewise still under investigation with habitat- and food web-specific trends apparent. Furthermore, there is a dearth of data detailing PFAS concentrations in avifauna near industrial point sources or potential impacts related to chronic elevated exposure from such direct or substantial discharges. ,, This stands as a significant data gap considering that effective protection of endangered species and habitats surrounding contaminated sites relies on understanding exposure and impacts in birds and other sensitive wildlife.…”
Section: Introductionmentioning
confidence: 99%
“…35−37 Furthermore, there is a dearth of data detailing PFAS concentrations in avifauna near industrial point sources or potential impacts related to chronic elevated exposure from such direct or substantial discharges. 29,30,38 This stands as a significant data gap considering that effective protection of endangered species and habitats surrounding contaminated sites relies on understanding exposure and impacts in birds and other sensitive wildlife.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Poly- and perfluoroalkyl substances (PFAS) are a family of human-made organofluorine compounds widely used in aqueous fire-fighting foams (AFFF), paper, textile, and cookware. Because of their wide use, the environmental leaching of PFAS is ubiquitous and poses grave potential environmental and public health threats: detectable serum PFAS was reported in virtually the entire US population (>95%) , and over six million Americans are possibly using drinking water sources with PFAS (perfluorooctanesulfonate (PFOS) and perfluorooctanoic acid (PFOA)) exceeding EPA’s lifetime health advisory …”
Section: Introductionmentioning
confidence: 99%